Adaptasi Program Kewirausahaan Usaha Mikro Kecil Menengah Dalam Mengentaskan Kemiskinan Oleh Badan Amil Zakat Nasional Kota Jambi - Rafi’i Rafi’i; Sucipto Sucipto; Maryani Maryani (Pusat Riset dan Inovasi Nasional, 2025)
The entrepreneurship adaptation program by BAZNAS Kota Jambi has shown its ability to adjust to field conditions, including through directives issued by the Mayor of Jambi. This study uses a descriptive qualitative method aiming to explore: the implementation of the adapted entrepreneurship program for MSMEs in alleviating poverty, the supporting factors, and how the program contributes to poverty reduction efforts. The findings indicate that BAZNAS Kota Jambi has distributed productive zakat funds through the